Relating Maxwell's demon and quantitative analysis of information leakage for practical imperative programs. (September 2017) - Anjaria, Kushal; Mishra, Arun
Abstract : Shannon observed the relation between information entropy and Maxwell demon experiment to come up with information entropy formula. After that, Shannon's entropy formula is widely used to measure information leakage in imperative programs. But in the present work, our aim is to go in a reverse direction and try to find possible Maxwell's demon experimental setup for contemporary practical imperative programs in which variations of Shannon's entropy formula has been applied to measure the information leakage. To establish the relation between the second principle of thermodynamics and quantitative analysis of information leakage, present work models contemporary variations of imperative programs in terms of Maxwell's demon experimental setup. In the present work five contemporary variations of imperative program related to information quantification are identified. They are: (i) information leakage in imperative program, (ii) imperative multithreaded program, (iii) point to point leakage in the imperative program, (iv) imperative program with infinite observation, and (v) imperative program in the SOA-based environment. For these variations, minimal work required by an attacker to gain the secret is also calculated using historical Maxwell's demon experiment. To model the experimental setup of Maxwell's demon, non-interference security policy is used. In the present work, imperative programs with one-bit secret information have been considered to avoid the complexity. The findings of the present work from the history of physics can be utilized in many areas related to information flow of physical computing, nano-computing, quantum computing, biological computing, energy dissipation in computing, and computing power analysis.